Factors Affecting Small and Medium-Sized Enterprises Financial Resilience Post Covid-19 Pandemic in South Africa - MSOMI, Thabiso Sthembiso; ZUNGU, Sphesihle Charles (PT Keberlanjutan Strategis Indonesia, 2023)
This research paper aims to investigate the factors influencing the financial resilience of SMEs in South Africa in the aftermath of the COVID-19 pandemic. The study focuses on three primary factors: access to loans, the interest rates applied to these loans, and the structure of repayment plans. To achieve this purpose, a quantitative research methodology, guided by the positivism philosophical framework, was employed. The research selected 310 respondents who were SME owners representing various sectors. The data collection and analysis methods primarily involved multivariate regression analysis. The research revealed that access to loans, interest rates on loans, and the design of repayment plans exerted positive and statistically significant effects on the financial resilience of SMEs in the post-COVID-19 period. These factors displayed probability values of 0.005 and absolute values of 0.448, 0.456, and 0.432, respectively. These findings underscore the crucial role of these factors in determining the financial stability of SMEs. The study's implications are twofold. First, it suggests that financial institutions should streamline the process for SMEs to access financing, making it more accessible and accommodating. Furthermore, these institutions should tailor loan repayment options to better align with the unique needs of SMEs. Second, the research underscores the importance of offering financial education and support services to assist SMEs in enhancing their financial management skills and adaptability within the post-pandemic economic landscape.